1987
DOI: 10.1515/ling.1987.25.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on code switching: how universal are they?

Abstract: Recently constraints on code switching have been postulated in studies using and/or justifying particular theoretical frameworks. This paper examines the constraints -structural integrity, free morpheme, government, semantic -and the notion of the 'matrix language'. It also looks at assumptions underlying the constraints -stability and 'sfandardness' of grammatical systems in contact, grammatically, the inclusion of trigger words as par t of the switch. It tests the constraints and their assumptions against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(102 citation statements)
references
References 10 publications
2
93
0
7
Order By: Relevance
“…We are indebted to many remarks and criticisms by others (Auer 1997;Clyne 1987). In particular, a much fuller version of many aspects discussed here can be found in Muysken (2000).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…We are indebted to many remarks and criticisms by others (Auer 1997;Clyne 1987). In particular, a much fuller version of many aspects discussed here can be found in Muysken (2000).…”
Section: Introductionmentioning
confidence: 75%
“…For example in Dutch-English CS, various function-words operate in this way, e.g. de/the and dat/that,or in which is common to both (Clyne 1987). Similarly, Treffers-Daller (1994), in her study of French-Dutch contact in Brussels, found that the two varieties shared numerous phonemes; and that many words, e.g.…”
Section: Some Reasons Why the Glove Does Not Fitmentioning
confidence: 94%
“…Algunos investigadores han propuesto que los cambios intra-oracionales solo pueden ocurrir cuando las estructuras gramaticales de las dos lenguas son congruentes, tanto antes como después del cambio (Poplack 1980;Lipski 1977Lipski , 1978Lipski , 1982Lipski , 1985; por lo tanto, no está claro si las restricciones postuladas responden a características universales de los pronombres, interrogativos, negativos, etc., o si son consecuencias de la falta de compatibilidad morfosintáctica entre determinadas lenguas (p. ej., Clyne 1987;Mahootian y Santorini 1996). En una investigación preliminar, para determinar si las restricciones postuladas sobreviven en la ausencia de discrepancias gramaticales, Lipski (2016a) realizó experimentos psicolingüísticos entre hablantes bilingües en Ecuador, cuyas lenguas eran quichua y chaupi lengua (media lengua), una lengua mixta con morfosintaxis del quichua pero con casi todas las raíces derivadas del español, incluso los pronombres, interrogativos y negativos (Muysken 1979(Muysken , 1981Gómez Rendón 2008).…”
Section: Algunas Restricciones Propuestas Sobre Los Cambios Intra-oraunclassified
“…Both terms are used for the same practice by some scholars, while others utilize it for the formal linguistic characteristics of language-contact phenomena. Meanwhile, code-switching refers to the actual, spoken usages by multilingual individuals (Bokamba & Eyamba, 1989;Clyne, 2000;Genessee, 2000). Woon (2007, p. 1) defined codemixing as "change of one language to another within the same utterance or in the same oral/written text".…”
Section: Definition Of Code-switchingmentioning
confidence: 99%